Birds as indicators of early Holocene biodiversity and the seasonal nature of human activity at WF16, an early Neolithic site in Faynan, Southern Jordan. (27th April 2022) - Mithen, Steven; White, Judith; Finlayson, Bill; Greet, Ben; Khoury, Fares
Abstract: Birds are useful indicators of biodiversity. Their bones have been used for reconstructing the local environments and seasonality of human activity at Epipalaeolithic and early Neolithic sites in south‐west Asia. We consider the bird bones from WF16, an early Neolithic settlement in southern Jordan, currently located in an arid environment. The settlement has elaborate pisé‐built architecture and material culture. The species represented in the WF16 avian assemblage suggest the environment was considerably wetter and more wooded than today, supporting the idea that early Holocene communities targeted locations with abundant and diverse resources. However, while the range of species at WF16 is equivalent to that found at other Epipalaeolithic and early Neolithic sites in the region, the diversity of the assemblage is strikingly limited, with a heavy dominance of raptors, notably buzzards. We suggest an annual pattern of seasonally based activities, with a relatively small resident population drawing on supplies of water during the winter months for constructing and maintaining site architecture and spring/autumn gatherings of people from across the region to hunt migratory raptors and undertake performance and ceremony at the settlement.